Sochi State University as a Driver of Event Volunteering in the Region - Aleksandr A. Ryabtsev; Tatyana A. Yudina; Sergey V. Сheremshanov; Georgy S. Papazyan (Moscow Polytechnic University, 2018)
The development of the volunteer movement is one of the important tasks of the state policy of modern Russia. Today, many universities create on their basis volunteer centers (EC), which are one of the best mechanisms for attracting young people to solving urgent problems of the development of society, an additional pedagogical and personal-developing resource. This article presents the results of the implementation by Sochi State University (SSU), which is a pillar higher education institution of the Krasnodar Territory, the strategic project "Resource Center for Event Volunteering", aimed at ensuring the sustainable development of volunteering in the region and the Russian Federation as a whole. Volunteering is viewed as an institution of civil society and the basis for implementing long-term socio-cultural projects. The article describes the experience of the SSU in the development of volunteerism in the region, the improvement of its resource provision, the establishment of cooperation in solving these problems with the authorities, administration and the management of volunteer organizations of pillar universities and the region. A flexible universal model of training volunteers and organizers of the volunteer movement, organizational and managerial conditions and scientific and methodological approaches to the organization of student volunteering are presented. The results of their implementation in the region are described. The authors substantiate the expediency of the creation of volunteering resource centers in the regions, providing educational organizations with a range of information, advisory and methodological services in the field of volunteering.